Implementation of Air Expansion Simulation (AES) in physics education to increase student interest in environmental issues - Febiana Dinda Puspita; Afif Jauhari; Iqbal Ainur Rizki; Sujito Sujito; Nurita Apridiana Lestari (Education and Development Research, 2026)
Increased pollution on Earth will cause environmental imbalance, which in turn will cause environmental damage. In addition, sustainable education is implemented to help address the problem by teaching students through direct experience. Therefore, a simple air expansion simulation is applied in sustainable physics learning as a simple demonstration of air velocity. With the implementation of sustainable physics education, it is hoped that students can understand air pressure and apply it in the environment to increase their interest in learning physics through environmental issues. Simple simulations are used to increase students' interest in learning physics. Based on the results obtained, the application of air expansion simulation (AES) as physics education increases students' interest and understanding, as shown by the results of responses that indicate strong agreement. Students can easily understand the material through simple air expansion simulations because during the learning process, students feel more interested. Students find it easier to understand because learning is done contextually, but learning is also done by involving students directly. Therefore, students find it easier to understand and master the material based on direct experience.